The mutual stereotype: eroticism in the narrative of Carmen Kurtz (XXI Century. Spanish Literature and Culture, 2019)
Carmen Kurtz is an author of the generation of half a century that has been partially forgotten. However, her work is very valuable and contains an interesting reflection on the situation of women in their time and, in a broader sense, on the inauthenticity of human relationships. In this work we study how eroticism is a ground of encounter and disagreement between men and women. In reality, both genders are subject to the premises of their own stereotype. Carmen Kurtz denounces in her works the stereotypes that prevent people from building a true identity. The following novels have been worked on: Duermen bajo las aguas (1955), La vieja ley (1956), El desconocido (1956), Detrás de la piedra (1958), Las algas (1966), En la punta de los dedos (1968) and Al otro lado del mar (1973).